Whole-Genome Sequencing of SARS-CoV-2 Infection in a Cluster of Immunocompromised Children in Indonesia - Putri, Nina Dwi; Johar, Edison; Dewi, Yora Permata; Indrasari, Nuri Dyah; Wulandari, Dewi; br Pasaribu, Merci Monica; Sari, Teny Tjitra; Cakti, Fitri Prima; Jasin, Madeline Ramdhani; Tartila, Tartila; Yudhaputri, Frilasita Aisyah; Malik, Safarina G.; et al. (Frontiers in Medicine, 2022)
Background: Thus far, Indonesia has recorded over 4,000,000 confirmed COVID-19 cases and 144,000 fatalities; 12.8% of cases have been in children under 18 years. Whole genome viral sequencing (WGS) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been demonstrated to help differentiate hospital-acquired infection from community-acquired coronavirus disease 2019 (COVID-19) infection. Our study highlighted the use of WGS to investigate the origin of infection among pediatric oncology patients at Jakarta. The aim of our study was to evaluate clinical and laboratory characteristics as well as the efficacy of using WGS to confirm hospital-acquired COVID-19 infection in a cluster of immunocompromised children within a single ward of a tertiary hospital in metropolitan Jakarta based on quasispecies, viral load, and admission dates. Method: Real-time reverse-transcription polymerase chain reaction (RT-PCR) from nasopharyngeal swabs was used to diagnose the patients as well as guardians and healthcare workers in the ward, followed by WGS of RT-PCR positive cases to establish their phylogenetic relationships. Result: Using WGS we showed that SARS-CoV-2 transmission in a cluster of children with underlying malignancy was characterized by high similarity of whole virus genome between cases, suggesting nosocomial transmission.